Mapping the evolution of neurofeedback research: a bibliometric analysis of trends and future directions - Wider, Walton; Mutang, Jasmine Adela; Chua, Bee Seok; Pang, Nicholas Tze Ping; Jiang, Leilei; Fauzi, Muhammad Ashraf; Udang, Lester Naces (Frontiers in Human Neuroscience, 2024)
This study conducts a bibliometric analysis on neurofeedback research to assess its current state and potential future developments. It examined 3,626 journal articles from the Web of Science (WoS) using co-citation and co-word methods. The co-citation analysis identified three major clusters: "Real-Time fMRI Neurofeedback and Self-Regulation of Brain Activity", "EEG-Neurofeedback and Cognitive Performance Enhancement", and "Treatment of ADHD Using Neurofeedback". The co-word analysis highlighted four key clusters: "Neurofeedback in Mental Health Research", "Brain-Computer Interfaces for Stroke Rehabilitation", "Neurofeedback for ADHD in Youth", and "Neural Mechanisms of Emotion and Self-Regulation with Advanced Neuroimaging". This in-depth bibliometric study significantly enhances our understanding of the dynamic field of neurofeedback, indicating its potential in treating ADHD and improving performance. It offers non-invasive, ethical alternatives to conventional psychopharmacology and aligns with the trend toward personalized medicine, suggesting specialized solutions for mental health and rehabilitation as a growing focus in medical practice.